1994
DOI: 10.1038/ki.1994.208
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of metalloproteinase transin induces aberrant behavior of cultured mesangial cells

Abstract: The aim of the present study is to clarify whether the cellular expression of a matrix-degrading metalloproteinase, transin, alters the behavior of cultured mesangial cells (MCs). The cDNA encoding rat transin was introduced into rat MCs and transcribed under the control of a Rous sarcoma virus promoter. The resulting transfectants were then investigated for cell shape, migration, proliferation, and expression of genes associated with matrix metabolism. Northern blot analysis routinely detected the transin tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Stromelysin is a matrix-degrading metalloproteinase that plays an important role in the deg-radation of extracellular matrix. Expression of stromelysin is induced in inflamed glomeruli (27) and associated with aberrant function of glomerular cells and the glomerular basement membrane (17,37). Cultured mesangial cells, as well as isolated glomeruli, express stromelysin in response to activated macrophages and macrophage-derived proinflammatory cytokines (14,16,18).…”
mentioning
confidence: 99%
“…Stromelysin is a matrix-degrading metalloproteinase that plays an important role in the deg-radation of extracellular matrix. Expression of stromelysin is induced in inflamed glomeruli (27) and associated with aberrant function of glomerular cells and the glomerular basement membrane (17,37). Cultured mesangial cells, as well as isolated glomeruli, express stromelysin in response to activated macrophages and macrophage-derived proinflammatory cytokines (14,16,18).…”
mentioning
confidence: 99%
“…Using techniques for three-dimensional culture, we previously reported that surrounding ECM elicits differentiation of mesangial cells in vitro [20, 21, 22]. A gene transfection study showed that mesangial cells with aberrant matrix-degrading activity exhibited an activated phenotype in ECM [23]. This line of evidence suggests that the mesangial matrix controls the behavior of mesangial cells and maintains their differentiation in the glomerulus.…”
Section: Tgf-β As An Endogenous Defender Against Glomerular Injurymentioning
confidence: 68%
“…A cell clone SM43 was established by a limiting dilutional method and identified as being of mesangial cell phenotype as described (25). By using a modified calcium phosphate coprecipitation method (26), SM43 mesangial cells were cotransfected with a regulator plasmid pUHD15-1 encoding tTA (21) and a plasmid pRc/CMV (Invitrogen) that introduces a neomycin phosphotransferase gene. Stable transfectants were selected in the presence of neomycin analogue G418 (750 ,ug/ml; Sigma).…”
Section: Methodsmentioning
confidence: 99%